PSYCHOLOGICAL RISK FACTORS FOR OVERUSE INJURIES IN ELITE ATHLETICS: A COHORT STUDY IN SWEDISH YOUTH AND ADULT ATHLETES. Issue 7 (11th March 2014) - Timpka, T; Jacobsson, J; Dahlström, Ö; Kowalski, J; Bargoria, V; Ekberg, J; Nilsson, S; Renström, P
Abstract : Background: There is growing evidence that athletes' psychological characteristics are of importance for understanding overuse injuries in sports. Objective: To examine the importance of psychological factors as risk indicators for sustaining athletics injuries. Design: Cohort study with 52 weeks duration. Setting: Swedish male and female youth and adult elite athletics athletes. Participants: Athletes ranked in the national top 10 in each event were invited to a one-year surveillance study. Among those consenting to participate (n=292), 73% (n=212) completed a psychological survey at baseline. Risk factor assessment: Event group, previous injury, training volume and intensity (measured by the TLRI), perceived motivational climate (PMCSQ), coping behaviors (Brief Cope), body consciousness and hyperactivity (BCS-ADHD), commitment to exercise (CES), and interactions with gender and age. Main outcome measurements: Time to first injury causing full or partial time loss from athletics. Results: 199 (68%) athletes reported an injury during the study period. Ninety-six percent of reported injuries were classified as associated with overuse. Cox proportional hazards regression analyses showed that maladaptive coping through self-blame (P=.001; HR 1.37 (95% CI 1.14–1.67)) and hyperactivity (P=.025; HR=1.01 (95% 1.00–1.02)) were associated with increased injury risk. Additionally, male adult athletes with a previous serious injury had an increased risk of injury (P=.043; HR=2.05 (95% CI 1.02–4.07)), while the injury risk was decreased for male(P=.032; HR=0.47 (95% CI 0.23–0.94)) and female (P=.025; HR=0.49 (95% CI 0.26–0.91)) adult athletes without previous injury. Conclusions: The psychological factors self-blame and hyperactivity earlier linked to non-suicidal self-injury in general populations were together with causal interactions combining previous injury, age and gender found to be related with overuse injury in athletics athletes. Further studies on associations between injury and indicators of depression and stress in elite athletics athletes are warranted.